The Frequency of Exfoliation Syndrome in the Central Anatolia Region of Turkey - Raşit Kılıç; Hafize Sezer; Sebile Ü. Çomçalı; Serdar Bayraktar; Gökay Göktolga; Yasin Çakmak; Abdi B. Çetin; Tongabay Cumurcu (Journal of Ophthalmology)
Aim. The aim of this study was to investigate the frequency of exfoliation syndrome in the Central Anatolia region of Turkey and to evaluate its relationship with cardiovascular and ocular diseases. Methods. Patients over the age of 45 years who presented to the clinic were included in the study. All cases underwent a comprehensive ophthalmology examination. Exfoliation syndrome was diagnosed with the presence of exfoliative material on the lens anterior capsule or iris on slit lamp examination. The patients were divided into two groups as the exfoliation syndrome group and nonexfoliation syndrome group according to the presence of exfoliative material. Results. Exfoliative material was found in one or both eyes of 212 of the 2103 patients (10.1%) evaluated within the scope of the study. A significant relationship was found between exfoliation syndrome and increasing age and male gender. A significant relationship was found between exfoliation syndrome and glaucoma, cataracts, age-related macular degeneration, and phacodonesis. While no relationship was found between exfoliation syndrome and hypertension or diabetes mellitus, a significant relationship was found with coronary artery disease. Conclusion. The unilateral or bilateral exfoliation syndrome frequency was 10.1% in this hospital-based study. A statistically significant relationship was found between exfoliation syndrome and advancing age, gender, and coronary artery disease.